Optical simulations in perovskite devices: a critical analysis - Kar, Shaoni (2023)
With halide perovskite gaining popularity for optoelectronics application, it is imperative to push for device stacks with minimum optical losses and maximum efficiency. However, the vast plethora of material systems and device architectures available through computerized combinatorial analysis made experimental trials for each proposed possibility impractical. Thus, high-throughput optical simulations in conjunction to comprehensive electronic modeling are necessary to predict outputs and minimize experimental efforts involved. Here, we aim to critically summarize some of the most intuitive and efficient approaches to optical modeling for perovskite-based devices and work toward a consensus on the best avenues to utilize these models. First, the nuances of ellipsometry measurements for ascertaining accurate optical constants of perovskite are discussed. Modeling techniques (such as ray tracing, transfer matrices, finite difference time domain, and finite element methods) to simulate the optical interaction within the device are then elaborated focusing on their advantages and limitations. Next, the primary challenges to attaining greater accuracy of optical constant data as well as insights on the future trends are identified. Finally, an interactive flowchart-based decision tree to ascertain the best simulation technique for a given optoelectronic device architecture is built, which will greatly help experimental scientists and beginners in optical modeling.